Styles of Landscape Design - B, Xo`jayorova O.; B, Kadirova SH.; Q, Ruziboyeva D. (Researchparks Publishing, 2023)
The choice of landscape design style is directly envy of the features of the site itself. Its configuration, dimensions and environment must be taken into account. Moreover, it is necessary to take into account the architectural style of the house itself and the structures on the territory. It is very important that everything looks harmonious.